2013
DOI: 10.1103/physreve.88.052118
|View full text |Cite
|
Sign up to set email alerts
|

Products of rectangular random matrices: Singular values and progressive scattering

Abstract: We discuss the product of M rectangular random matrices with independent Gaussian entries, which have several applications, including wireless telecommunication and econophysics. For complex matrices an explicit expression for the joint probability density function is obtained using the Harish-Chandra-Itzykson-Zuber integration formula. Explicit expressions for all correlation functions and moments for finite matrix sizes are obtained using a two-matrix model and the method of biorthogonal polynomials. This ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
371
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 176 publications
(384 citation statements)
references
References 56 publications
(162 reference statements)
8
371
0
5
Order By: Relevance
“…This was extended by Akemann, Ipsen and Kieburg [4] to the general rectangular case. The determinantal point process is a biorthogonal ensemble [13] with joint probability density function (see [4, formula (18)])…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 98%
See 4 more Smart Citations
“…This was extended by Akemann, Ipsen and Kieburg [4] to the general rectangular case. The determinantal point process is a biorthogonal ensemble [13] with joint probability density function (see [4, formula (18)])…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 98%
“…Very recently, Akemann, Kieburg, and Wei [5] found that the squared singular values of products of complex Ginibre matrices are a determinantal point process on the positive real line. This was further extended to the case of products of rectangular Ginibre matrices by Akemann, Ipsen and Kieburg [4]. The correlation kernels in [2,3,4,5,25] are all expressed in terms of Meijer G-functions.…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 99%
See 3 more Smart Citations